Atypical cutaneous sporotrichosis in an immunocompetent adult: Response to potassium iodide - Nikita Gandhi; Ram Chander; Arpita Jain; Sarita Sanke; Taru Garg (Wolters Kluwer Medknow Publications, 2016)
Cutaneous sporotrichosis, also known as "Rose Gardener's disease," caused by dimorphic fungus Sporothrix schenkii, is usually characterized by indolent nodular or nodulo-ulcerative lesions arranged in a linear pattern. We report bizarre nonlinear presentation of Sporotrichosis, in an immunocompetent adult occurring after a visit to Amazon rain forest, speculating infection with more virulent species of Sporothrix. The diagnosis was reached with the help of periodic acid-Schiff positive yeast cells and cigar shaped bodies seen in skin biopsy along with the therapeutic response to potassium iodide.